PERAN KOLEGIUM BERDASARKAN UU NO.17 TAHUN 2023 - Gunawan Widjaja (Jurnal Kesehatan, 2026)
Law No. 17 of 2023 on Health revolutionises the management of the Indonesian health professions through the introduction of the College as an independent body of health science experts and an auxiliary body of the Council (Article 1(106), Article 272), aiming to improve the quality of medical and health personnel through competency standards, training curricula, and the development of evidence-based branches of science. This normative literature review analyses two main topics: first, the legal status of the College as a semi-autonomous entity under the President, distinct from conventional professional organisations, supported by Constitutional Court Decision No. 111/PUU-XXII/2024 and the Supreme Court; secondly, the implications and dynamics of its implementation, including transitional controversies, synergy with the Indonesian Health Council, and challenges posed by secondary regulations such as Ministry of Health Regulation No. 12 of 2024. The findings confirm that the College strengthens good governance in health through scientific independence, although harmonisation of regulations is required for optimal implementation to support national resilience and equitable service delivery.